ANALISIS PENGARUH DANA PIHAK KETIGA,NON PERFORMING LOAN, DAN SUKU BUNGA PINJAMAN TERHADAP PENYALURAN KREDIT MODAL KERJA, INVESTASI, DAN KONSUMSI BANK PEMBANGUNAN DAERAH (PERIODE 2003-2013) - Binangkit, Yogi Lingga (Jurnal Ilmiah Mahasiswa FEB, 2014)
This study aimstodetermine the effect ofthird-party  funds(DPK),  non-performing loan(NPL), andinterest rates on loans(SB)  onworking capital loans,  investment,  andconsumptioninthe RegionalDevelopment BanksthroughoutIndonesiain the period2003-2013.  This research isdescriptiveandquantitativedata usedare secondary dataandquarterly.  Method ofmultiple linear regressionanalysis usingOLS. Researchresultsshowedthat simultaneousDPK, NPL,  andSBhasa significant effect onthe variableworking capital loans,  investment,  andconsumption.  Inparisalworking capital loanssignificantly affectedbyDPK(+),  NPL(+)  andinterest rates(-),  theinvestmentcredit significantly affectedby DPK(+)  andinterest rates(-),  and consumer credit significantlyinfluencedbyDPK(+)  ,NPL(-),  and theinterest rate(+).  In general,variabledepositsarethe mostdominant influence oncredit.  The ratecoefficient of determination  (R2)for thevariablesthat affectworking capital loansamounted to97.1%, which means  the freevariablesin  the model isable to explainthe variableworking capital loansat 97.1%, the remaining2.9%  is explainedbyvariablesoutside the modelthis.  as well asthe levelof investmentcreditof  R2is 93.7% , the remaining  6.3%  explained byvariablesoutside the model, consumer loanhas  R2in the amount of97.7%, and the remaining  2.3%  explained byvariablesoutsidethe model. Keywords : Credit, Deposit, NPL, Interestrate